Test of my life: from cricket to cancer and back - "Sing , Yuvraj" (Noida, 2013)
For the first time ever, Yuvraj Singh tells the real story behind the 2011 World Cup when his on-the-field triumphs hid his increasingly puzzling health problems and worrying illnesses. In his debut book, The Test of My Life, he reveals how-plagued with insomnia, coughing fits that left him vomiting blood and an inability to eat-he made a deal with God. On the night before the 2011 ICC Cricket World Cup final, Yuvraj prayed for the World Cup in return for anything God wanted. In this book, he lays bare his fears, doubts and the lows he experienced during chemotherapy-when he lost his energy, his appetite and his hair-and his battle to find the will to survive. Poignant, personal, and moving, The Test of My Life is about cancer and cricket; but more importantly, it is about the human will to fight in the face of adversity and triumph despite all odds.
Keywords: Autobiography